Assessment of fluidized bed gasification of grapefruit solid waste. (September 2021) - Robaina, Boris Abel Ramos; Reyes, Yanet Guerra; Trujillo, Leonardo Aguiar; Montesino, Francisco Márquez; Pedroso, Daniel Travieso; Machin, Einara Blanco; Machín, Adrian Blanco; Pascual, Rodrigo; Pérez, Jesús Arauzo; Callejo, Alberto Gonzalo; Cebrian, José Luis Sánchez
Abstract: This work assesses the effects of various process temperatures (700, 750, and 800 °C) and equivalence ratio (0.25; 0.30 and 0.35) on gasification of grapefruit (Citrus x paradisi) solid waste (GSW) in a fluidized bed reactor. The experimental results permit the construction and fit tridimensional chart to assess the studied main output variables' behavior for the simultaneous variation of equivalence ratio and process temperature. The better producer gas composition for the grapefruit solid waste gasification was obtained for a process temperature of 800 °C and 0.25 equivalence ratio; the gas yields around 67%, with LHV of 4389 kJ/Nm 3, within the spectrum of values reported for other lignocellulosic residues. According to the obtained study results, GSW presents a valuable renewable energy resource for agroindustry. For operation parameters assessed, could be potentially produced 3.49 GJ of thermal energy per ton of GSW gasified. Graphical abstract: Unlabelled Image Highlights: Lab-scale fluidized bed gasification of grapefruit solid waste was characterized. Experimental behavior for the output variables was modeled. The better results were obtained for a PT of 800 °C and 0.25 equivalence ratio. The gas yields round 67%, with LHV of 4389 kJ/Nm 3 .